THE USE OF TECHNOLOGY IN TEACHING PHYSICS TO STUDENTS WITH DISABILITIES: A SYSTEMATIC REVIEW - Frank Angelo Pacala (Інформаційні технології і засоби навчання)
In recent years, incorporating technology into education for students with disabilities has significantly improved learning experiences and academic achievement. However, there remains a need for a deeper understanding of the most effective methods for using these technologies, particularly in physics education. This systematic review aims to consolidate research on the use of technology to support learning for students with disabilities, assess its effectiveness in improving educational outcomes, and identify areas for further study. The review focuses on the constructs, technological interventions, research gaps, limitations, and key findings from selected articles. The PRISMA framework was used to analyze research from databases, including EBSCO Host, Elsevier Science Direct, Emerald Insight, ProQuest, Google Scholar, ERIC, and Clarivate Analytics Web of Science. Out of 892 articles initially identified, 13 met the inclusion and exclusion criteria and validation from the experts. The most commonly studied disability was visual impairment, followed by intellectual disabilities. Most studies focused on learner achievement, with engagement and participation as secondary themes. The technologies used included assistive tools like web-based platforms, virtual and augmented reality (AR), and interactive learning systems. These adaptive technologies improved student involvement, social integration, and interest in science. Augmented reality, in particular, enhanced academic performance and knowledge retention, making it an effective tool for inclusive physics education. The findings indicate a growing trend towards integrating technology in inclusive education, emphasizing the role of personalized tools in improving accessibility and engagement for students with disabilities in physics.